Agrotourism and Sustainable Development in the Natural Reserve Tingana-Perú - García Palacios, María Alejandra; Barraza Lino, Roberto Pablo; Henderson Fartolino, Martin; Manchego Guerra, José Renatto; Aguirre-Camarena, Richard (LACCEI, 2025)
Abstract – Objective: To determine the relationship between agrotourism and sustainable development in the Tingana Natural Reserve, Peru. Method: The methodology had a quantitative approach, applied type, correlational level, cross-sectional design, and non-experimental design. The sample size consisted of 23 heads of household, selected through intentional sampling. The data collection technique was a survey, and the instrument was a questionnaire composed of 24 items with structured Likert scale responses. The instrument’s validity was assessed by three expert judges. Data were analyzed using SPSS v26 software. Results: Spearman’s Rho statistic was used to test the general hypothesis, revealing a moderate correlation (Rho = 0.434). The analysis also identified the relationship between agrotourism and the dimensions of sustainable development, with Spearman’s Rho coefficients as follows: environmental factor (Rho = 0.156), social factor (Rho = 0.398), and economic factor (Rho = 0.226). Conclusions: It is concluded that there is a moderate relationship between agrotourism and sustainable development in the Tingana Natural Reserve, Peru.